2020
DOI: 10.3390/ijerph17155333
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Measured by EQ-5D in Relation to Hospital Stay and Readmission in Elderly Patients Hospitalized for Acute Illness

Abstract: We evaluated the predictability of self-reported Health-related quality of life (HRQoL) assessed by the 3-level 5-dimensional Euro-Quality of Life tool (EQ-5D-3L) and the EQ-Visual Analog Scale (EQ-VAS) on clinical outcomes of elderly patients who were admitted to an acute geriatric ward. A total of 102 participants (56.9% men) with a median age of 81.0 years (interquartile range or IQR: 76.0–85.3 years) were studied. The age-adjusted Charlson comorbidity index was 5.0 (IQR: 4.0–6.0) with a median length of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Studies reported development of novel or adapted instruments for people receiving palliative care in Canada [ 24 ] and for older people being discharged from hospitals in the USA, Ireland, and Switzerland [ 25 ]. Other studies from the UK [ 26 ], Netherlands [ 27 ], and France [ 28 ] evaluated instruments for conceptual overlap and convergent validity, while interrater comparison or outcome prediction studies were performed in Australia [ 29 ], UK [ 30 ], Sweden [ 31 ] and Taiwan [ 32 ]. Although developed as a condition-specific measure, the QoL-AD was included at this stage as one study examined its collection from participants who did not necessarily have cognitive impairment [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported development of novel or adapted instruments for people receiving palliative care in Canada [ 24 ] and for older people being discharged from hospitals in the USA, Ireland, and Switzerland [ 25 ]. Other studies from the UK [ 26 ], Netherlands [ 27 ], and France [ 28 ] evaluated instruments for conceptual overlap and convergent validity, while interrater comparison or outcome prediction studies were performed in Australia [ 29 ], UK [ 30 ], Sweden [ 31 ] and Taiwan [ 32 ]. Although developed as a condition-specific measure, the QoL-AD was included at this stage as one study examined its collection from participants who did not necessarily have cognitive impairment [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients’ general demographic data were obtained from patients’ medical records, and included age, sex, body mass index (BMI), lifestyle habits, education level, marital status, and socioeconomic status. We further assessed patients’ medical histories and comorbidities and recorded any diagnosed diseases, medications, and age-adjusted Charlson comorbidity index (ACCI) scores [ 9 ]. At both admission and discharge, all participants were evaluated by a comprehensive geriatric assessment (CGA), as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…At both admission and discharge, all participants were evaluated by a comprehensive geriatric assessment (CGA), as previously described. [ 9 ] Cognitive status was measured using MMSE, with scored ranging from 0 to 30, that was conducted by well-trained nurses. The normal and abnormal cognitive function cut-off points, as defined according to Taiwanese–Mini-Mental State Examination (T–MMSE), was adjusted based on age and educational level.…”
Section: Methodsmentioning
confidence: 99%
“…At admission, general demographic data of the participants, including lifestyle habits, age, gender, body mass index, social, and family histories and medical histories, including diagnosed diseases and medications, were recorded. Moreover, at baseline, and every 3 months thereafter, a Chinese version of CGA was conducted by the registered nurse for each participant to evaluate underlying geriatric problems and changes after DCS [ 13 ]. If the participants had medical, functional, and/or social difficulties, they were referred to geriatricians, dietitians, rehabilitation therapists, psychiatrists, or social workers, as appropriate.…”
Section: Methodsmentioning
confidence: 99%